KH Integration of AI Applications in High School Physics, Kolb’s Convergent Style - Kemouss, Hassane; Abdannour, Omar; Mohamed, Khaldi (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
This study explores the integration of artificial intelligence (AI) applications in physics teaching at the secondary level. An interactive approach based on Kolb's learning model; The authors evaluated the convergent style of the kolb cycle with the use of simulations and AI-based data analysis systems to improve students' understanding of abstract physics concepts. The results show that these AI tools allow a more intuitive visualization of phenomena and facilitate the interpretation of experimental data. Students who used these resources demonstrated better performance and greater engagement with the subject. This research highlights the potential of AI to enrich physics learning in high school and opens the way to new innovative educational approaches.